Organizational structure, human capital and collaboration networks: determinants of innovation capability in restaurants (2018)
Innovation capability is the skill to absorb; combine and transform specific organizational resources to generate value above the market average; such as structure; people and relationships. For this reason; the paper aim is to analyze organizational structure; human capital and collaboration networks as determinants of innovation capability in restaurants in Playa del Carmen; a tourist destination in the Mexican Caribbean. A quantitative methodology was followed; using the Pearson coefficient and structural equation modeling (SEM) for hypothesis testing. The results confirmed that collaboration networks with universities; government organisms and other tourism companies enhance the organizational structure and human capital. It is concluded that restaurants should rethink their strategies to improve their innovation capability from their organizational structure and collaboration networks being excellent predictors of human capital for the generation and development of ideas.